Genomic and proteomic advances in autism research - Maurer, Martin H. (Electrophoresis, 2012)
Recent studies suggest that adult neural stem cells (NSCs) may play a role in the pathogenesis of a number of the developmental disorders subsumed under the term autism spectrum disorders (ASD) that have in common impaired social interaction, communication deficits, and stereotypical behavior or interests. Since there is no “unifying hypothesis” about the etiology and pathogenesis of ASD, several factors have been associated with ASD, including genetic factors, physical co-morbidity, disturbances of brain structure and function, biochemical anomalies, cognitive impairment, and disorders of speech and emotional development, mostly the lack of empathy. Most of disturbances of brain interconnectivity are regarded as main problem in autism. Since NSCs have a distinct life cycle in the mammalian brain consisting of proliferation, migration, arborization, integration into existing neuronal circuits, and myelinization, disturbances in NSCs differentiation is thought to be deleterious. In the current review, I will summarize the results of genomic and proteomic studies finding susceptibility genes and proteins for autism with regard to NSCs differentiation and maturation.
Gesehen am 25.10.2018